Development of a multiplexed opsonophagocytic killing assay (MOPA) for group B Streptococcus. Issue 1 (2nd January 2018) - Choi, Min Joo; Noh, Ji Yun; Cheong, Hee Jin; Kim, Woo Joo; Lin, Shun-Mei; Zhi, Yong; Lim, Jae Hyang; Lim, Sangyong; Seo, Ho Seong; Song, Joon Young
ABSTRACT: Group B Streptococcus (GBS) is a leading cause of sepsis in infants as well as chorioamnionitis in pregnant women. Opsonophagocytic killing assays (OPAs) are an essential technique in vaccine studies of encapsulated bacteria for estimating serotype-specific functional antibody levels in vitro . Here, we developed a three-fold multiplexed OPA (MOPA) to enable practical, large-scale assessment of GBS vaccine immunogenicity, including against serotypes Ia, III, and V. First, three target bacteria strains resistant to streptomycin, spectinomycin, or kanamycin were generated by natural selection through exposure to increasing antibiotic concentrations. Since a high level of nonspecific killing (NSK) of serotype V was observed in a 12.5% baby rabbit complement (BRC) solution, the BRC concentration was optimized. The final GBS-MOPA BRC concentration was 9%, which resulted in less than 20% NSK. The specificity was measured by preabsorbing serum with inactivated GBS. The opsonic index (OI) of preabsorbed serum with the homologous serotype GBS was significantly reduced in all three serotypes tested. The accuracy of the MOPA was compared with that of a single OPA (SOPA) with 35 serum samples. The OIs of the MOPA correlated well with those of the SOPA, and the r 2 values were higher than 0.950 for all three serotypes. The precision of the MOPA assay was assessed in five independent experiments with five serum samples. The inter-assay precision of the GBS-MOPA was 12.5% of the average coefficient of variation. This is the first report to develop and standardize a GBS-MOPA, which will be useful for GBS vaccine development and evaluation.